Data-driven innovation : why the data-driven model will be key to future success - Andersen, Michael Moesgaard; Pedersen, Torben (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Today, innovation does not just occur in large and incumbent R&D organizations. Instead, it often emerges from the start-up community. In the new innovation economy the key is to quickly find pieces of innovation, some of which may already be developed. Therefore, there is need, for more advanced means of searching and identifying innovation wherever it may occurs. We point to the importance of data-driven innovation based on digital platforms, as their footprints are growing rapidly and in sync with the shift from analogue to digital innovation workflows. This book offers companies insights on paths to business success, and tools that will help them find the right route through the various options when it comes to the digital platforms where innovations may be discovered and from which value may be appropriated. The world hungers for growth and one of the most important vehicles for growth is innovation. In light of the new digital platforms from which data-driven innovation can be extracted, major parts of analogue workflows will be substituted with digital workflows. Data-driven innovation and digital innovation workflows are here to stay. Are you?"--
OCLC-licensed vendor bibliographic record.
Keywords: Business -- Technological innovations; Success in business; Big data -- Economic aspects; BUSINESS & ECONOMICS / Entrepreneurship; COMPUTERS / Database Management / General